Foreign Direct Investment Dynamics and Economic Growth in the Case of India - Sadashiv, Kharat Rahul (Journal of Business and Economic Options, 2023)
This research endeavor delves into the pivotal role of foreign direct investment in propelling the development trajectory of the Indian economy—a nation renowned for its status as a prime recipient of foreign direct investment inflows. Foreign direct investment serves as a linchpin for catalyzing growth across diverse sectors, ranging from primary industries to tertiary services, thereby exerting a transformative impact on India's economic landscape. Central to the efficacy of foreign direct investment is its capacity to augment productivity by facilitating the infusion of financial resources, technology, and innovative managerial practices—a symbiotic exchange that redounds to the benefit of both domestic enterprises and foreign investors. By leveraging foreign direct investment inflows, Indian firms can avail themselves of cutting-edge technologies, enhance operational efficiencies, and unlock new avenues for growth and expansion. Against this backdrop, this research paper seeks to unravel the multifaceted dynamics underpinning the nexus between foreign direct investment inflows and key macroeconomic indicators, notably gross domestic product growth and employment generation. Through a comprehensive analysis of empirical data and theoretical frameworks, the study endeavors to elucidate the nuanced mechanisms through which foreign direct investment contributes to India's economic advancement. One salient focus of this research is the examination of how foreign direct investment inflows catalyze expansionary impulses within the Indian economy, thereby fostering robust GDP growth trajectories. By channeling capital towards productive investments, fostering technology transfers, and stimulating competition and innovation, foreign direct investment serves as a potent driver of economic expansion, underpinning India's aspirations for sustained prosperity and development. Moreover, the research delves into the intricate interplay between foreign direct investment inflows and employment dynamics—a critical facet of India's developmental narrative. Through the creation of job opportunities, skill enhancement initiatives, and spillover effects across ancillary sectors, foreign direct investment exerts a tangible impact on employment generation, thereby bolstering livelihoods and fostering socio-economic inclusivity. By shedding light on these critical dimensions, this research paper aims to underscore the pivotal role of foreign direct investment as a catalyst for India's economic development journey. Through empirical analyses, policy prescriptions, and strategic insights, the study seeks to inform policymakers, stakeholders, and investors alike about the imperatives of fostering an enabling environment for foreign direct investment inflows, thereby unlocking the full potential of India's burgeoning economy.